If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 2 + 14 = 3x Reorder the terms: 2 + 14 + -5x = 3x Combine like terms: 2 + 14 = 16 16 + -5x = 3x Solving 16 + -5x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 16 + -5x + -3x = 3x + -3x Combine like terms: -5x + -3x = -8x 16 + -8x = 3x + -3x Combine like terms: 3x + -3x = 0 16 + -8x = 0 Add '-16' to each side of the equation. 16 + -16 + -8x = 0 + -16 Combine like terms: 16 + -16 = 0 0 + -8x = 0 + -16 -8x = 0 + -16 Combine like terms: 0 + -16 = -16 -8x = -16 Divide each side by '-8'. x = 2 Simplifying x = 2
| y/3+1=7 | | s+3.5s+20=65 | | -x-5y+6z=-24 | | 10x-9+6x=3x-2+7 | | 3*-3-5*0=a | | 14p=p^2-51 | | 1/315+6=30 | | 5x-4y+2z=21 | | X+9=30-2x | | Y=-12-4*(-3) | | 1/3m+6=15 | | C^2-50=-23k | | 45+37=82 | | -2r+s+4t=-9 | | 3x-5*(-12-4x)=-9 | | 24=k^2-10k | | x+3/5=x+7/12 | | 17x-186=3x+5 | | n/2-20=6 | | x+7=-3x+4 | | 4x+114+2x-156=180 | | -5*w^2+51=6 | | -6*(2/3)+3 | | (2a^2-0.3)(2a^2+0.3)= | | x*8-66=2x | | -3*(2/3)+5=y | | -9+6x=5-x | | 2(x-3)+5=6x-4(-1+x) | | -6x+(-3x+5)=-1 | | 43=6(x*x)-5x | | 10+22/7 | | 22/7-78 |